The relationship between attitudes, emotions and the intention to use the digital rehabilitation solution: Insights from Rwandan rehabilitation professionals - Kaisa Lällä; Michael Oduor; Eeva Aartolahti; David Tumusiime; Katariina Korniloff (Finnish Journal of eHealth and eWelfare)
Limited access to rehabilitation is a major challenge in low- and middle-income countries (LMIC). Digital rehabilitation (DR) has the potential to decrease this gap by offering effective and safe rehabilitation services for clients. This study aimed to investigate the relationship between rehabilitation professionals’ emotions and attitudes and intention to use the DR solution. Data was collected during two time periods in Rwanda: from July to November 2022, and from October 2023 to January 2024. A total of 58 rehabilitation professionals (67% men) completed the online survey at the beginning of the implementation of the DR solution and out of those, 23 (40%) responded to the follow-up survey. Attitudes were explored using Information Technology Attitude Scales for Health (ITASH), divided into three categories: 1) negative, 2) neutral, and 3) positive. Emotions were explored using an emotional scale with two factors “distress” and “positive arousal”. The intention to use the DR solution was assessed using a seven-point Likert scale, divided into three categories: 1) will not continue (points 1 to 3), 2) neutral (point 4), and 3) will continue (points 5 to 7). Crosstabs and Chi-Square were used to evaluate dependence between attitude and intention to use the DR solution. Binary logistic regression was used to assess the relationship between distress and positive arousal and intention to use the DR solution. Initially 91% of respondents had a positive attitude toward DR (M = 64, SD = 6.3). and positive attitude remained (M = 57, SD = 7.3, p = .860) at follow-up. A significant relationship between positive attitude and intention to use the DR solution (ꭓ2 = 18.33, p < 0.001) was found. Positive arousal was significantly related to a higher intention to use the DR solution (OR = 1.29, p = .008), while distress was not (OR = .89, p = .22). Distress decreased significantly (M = 9.7, SD = 3.0, p = .02) during the follow-up. The results do not definitively determine a relationship between attitudes, emotions, and the use of the DR solutions. However, positive emotions and attitudes appear to be linked to a higher intention to use the DR solution. Further research with a larger population is needed to confirm the relationship between emotions, attitudes, and use of the DR solutions in LMIC context.